El A. B. C. de la doctrina social católica - Cortés, Luis; Sobreroca, Luis A. (ECA: Estudios Centroamericanos, 1962)
No hay resúmenes disponibles. ECA Estudios Centroamericanos, Vol. 17, No. 173, 1962: 279-285.